2023
DOI: 10.1111/petr.14558
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in pediatric liver transplant recipients receiving bilateral continuous erector spinae plane blocks

Abstract: BackgroundRegional anesthesia allows for opioid‐sparing and enhanced recovery after many major surgeries. Erector spinae blockade, with reduced bleeding risk and the option for continuous infusion, offers an opportunity to promote this principle in pediatric liver transplant patients. Our goal was to evaluate pain scores, opioid use, and return of bowel function following continuous ESP blockade in pediatric liver transplant recipients.MethodsThis retrospective cohort study included extubated patients who rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…A recent study by Dewey et al . [ 14 ] in paediatric liver transplant, recipients also concluded that the use of continuous ESP catheter technique resulted in lesser post-surgical opioid consumption. However, unlike our study, they compared the ESP technique with standard IV analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Dewey et al . [ 14 ] in paediatric liver transplant, recipients also concluded that the use of continuous ESP catheter technique resulted in lesser post-surgical opioid consumption. However, unlike our study, they compared the ESP technique with standard IV analgesia.…”
Section: Discussionmentioning
confidence: 99%